Temporal trends of maternal near miss in Brazil between 2000 and 2012 - Beatriz Aguiar da Silva Carvalho; Ana Gabriella Bandeira Freire Andrade; Andreza Saboia Dantas; Ingrid Medeiros de Figueiredo; Jéssica Alves da Silva; Tatyana Souza Rosendo; Angelo Giuseppe Roncalli
Abstract Objectives: to identify the temporal trends and regional variations in maternal near miss in Brazil. Methods: ecological study of temporal trends. The units of analysis are in the States, the regions and Brazil, between 2000 and 2012, the dependent variable being the maternal near miss rate (MNMR), calculated from the records of the Sistema de Informações Hospitalares do Sistema Único de Saúde (SIH-SUS) (National Health Hospital Information System).Regression analysis using Joinpoint regression software, version 4.1.0. was applied to analyze morbidity trends. Results: the main result of this study was a finding on an increase rate trend in maternal near miss in Brazil, between 2000 and 2012. This trend behaves differently depending on the development level of the region studied, presenting a positively higher increase in less developed regions and states. Conclusions: there is an increasing trend in maternal near miss rates in Brazil. The SIH-SUS may be an important instrument in identifying and monitoring maternal morbidity. Furthermore, investments in more effective public policies are needed to reduce inequalities and improve human development, both of which have influenced the chain of events related to maternal health.